Which is more important to sorghum production systems in the Sudano-Sahelian zone of West Africa: Climate change or improved management practices?. (November 2020) - Adam, Myriam; MacCarthy, Dilys Sefakor; Traoré, Pierre C. Sibiry; Nenkam, Andree; Freduah, Bright Salah; Ly, Mouhamed; Adiku, Samuel G.K.
Abstract: The productivity of smallholder farming systems is held back by poor soil fertility, low input levels and erratic rainfall distribution in the sorghum-based cropping systems of the Sudano-Sahelian zone of West Africa. We assessed the sensitivity of current agricultural practices to climate change and to improved management practices: (i) increased fertilizer application combined with increased plant populations and (ii) use of improved sorghum varieties. We applied the Decision Support Systems for Agro-Technological Transfer (DSSAT) Cropping Systems Model, and the Agricultural Production Systems sIMulator (APSIM), for a multiple-farm assessment (i.e. diverse types of management and soils) in Koutiala (Mali) and Navrongo (Ghana), which are representative sites for West African sorghum production systems. Baseline climate data from observed weather (1980–2009) and future climates from five Global Circulation Models (GCMs: 2040–2069) in two Representative Concentration Pathways (RCP 4.5 and 8.5) were used as inputs for crop models. In Navrongo, under current management, sorghum yields either decreased or increased compared to the baseline, depending on the crop models and the GCMs; changes in management options induced a yield increase of up to 256%. The addition of genetic improvement resulted in further yield increases (24%). In Koutiala, sorghum yield changes for future climates ranged from −38 to +8% assuming current management. Shifting to an improved cultivar had a marginal effect on grain yields, while increased fertilizer rates resulted in grain yield increases ranging of 20% and 153% for DSSAT and APSIM, respectively, assuming the current climate. We conclude that in the Sudano-Sahelian zone of West Africa sorghum, as it is cultivated today, appears moderately vulnerable to climate change, while doubling fertilizer inputs with an adjusted planting density, in the current climate, would more than double yields. However, by exploring farm diversity we established that, under certain conditions, the effect of the future climate might be as important as the effect of management changes in the current climate, hinting at the importance of locally-relevant management practices. Highlights: Models gave different sensitivities to temperature and nitrogen, but responded similarly to CO2 and water. Based on these results, sorghum appears moderately vulnerable to likely changes in 2050 climate. Management variability had a greater influence on yield variability than did weather. Management practices outweigh the impact of 2050 climate change on sorghum grain yield. Understanding why differences in model performance under climate change are arising is essential.